Typification of Mattirolella silvestrii (Ophiostomatales, Ascomycota) - Ferretti-Cisneros, Nathalia U.; Souza, Priscilla S.; Barbosa, J. Renato C.; Lima, Rivete S.; Vasconcellos, Alexandre; Wartchow, Felipe (Phytotaxa, 2023)
Mattirolella S. Colla (1929: 44) is a genus of anamorphic fungi belonging to Sordariomycetes, Ascomycota (Wijayawardene et al. 2020), and is an apparent exclusive ectoparasite of the termite, Rhinotermes marginalis Linnaeus (1758: 550). It is traditionally treated as having a sporodochial to acervular conidiomata, with specialized basal cells forming haustoria that penetrate the tegumentum of the host, causing hypertrophy of the epiderm (Colla 1929, Khan & Kimbrough 1974a). Later, the morphology of Mattirolella was revisited and considered as forming thin and compact haustoria (Khan & Kimbrough 1974b) under a chambered and beaked ‘pycnidium’ (Kimbrough & Thorne 1982). Here we treat the conidiomata of M. silvestrii as a pycnothyrium (see Hughes 1953, Kirk et al. 2008).